2022
DOI: 10.3390/plants11040571
|View full text |Cite
|
Sign up to set email alerts
|

Sprouts and Microgreens—Novel Food Sources for Healthy Diets

Abstract: With the growing interest of society in healthy eating, the interest in fresh, ready-to-eat, functional food, such as microscale vegetables (sprouted seeds and microgreens), has been on the rise in recent years globally. This review briefly describes the crops commonly used for microscale vegetable production, highlights Brassica vegetables because of their health-promoting secondary metabolites (polyphenols, glucosinolates), and looks at consumer acceptance of sprouts and microgreens. Apart from the main crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 169 publications
2
78
0
Order By: Relevance
“…Brassica vegetables are known to contain high levels of vitamins, minerals, dietary fiber, phenolic compounds, and unique compounds, glucosinolates. Sprouts and microgreens of Brassica vegetables have gained acceptance in the population with health concerns because of their health-promoting secondary metabolites and higher nutritional value than those in their mature-leaf counterparts 80 82 . One study reported nutritional contents per 100 g of the edible portion of microgreens from R. sativus var.…”
Section: Discussionmentioning
confidence: 99%
“…Brassica vegetables are known to contain high levels of vitamins, minerals, dietary fiber, phenolic compounds, and unique compounds, glucosinolates. Sprouts and microgreens of Brassica vegetables have gained acceptance in the population with health concerns because of their health-promoting secondary metabolites and higher nutritional value than those in their mature-leaf counterparts 80 82 . One study reported nutritional contents per 100 g of the edible portion of microgreens from R. sativus var.…”
Section: Discussionmentioning
confidence: 99%
“…When nitrogen and manure are applied, the Jindong 22 cultivar is improved, and the total chlorophyll is higher than that of the Zhongmai 175 cultivar. Winter-wheat leaves improve the absorption of blue violet light by improving the comparative content of chlorophyll, thus improving the utilization of the small amount of light for crops in weak light [ 45 , 46 ]. Moreover, the chloroplast’s capacity to reduce chemical compounds is improved, and the content of light-collecting developments of green plants and the movement of the photosynthetic organic method are better [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemicals (e.g., carotenoids and phenolics) are found in significant amounts in microgreens [22]. Carotenoids possess antioxidant activity and play important physiological roles in the human body [106].…”
Section: Bioactive Compound Analysismentioning
confidence: 99%
“…However, the advantages of hydroponic platforms and the development of evaluation protocols can lead to a positive influence on the quality of microgreens with higher concentrations of active substances [18,19] and nutrients valuable for human health [20][21][22]. This is why it is necessary to standardize certain cultivation protocols to ensure their quality [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation